Analisis Kemampuan Literasi Sains Peserta Didik Kelas VIII SMPN Katumbagan Lemo Kab. Polewali Mandar Sulawesi Barat (Studi pada Materi Pokok Sistem Pencernaan) - Nur Maulidna Devi; Hasanuddin Hasanuddin; Arie Arma Arsyad (Universitas Negeri Makassar, 2026)
This study was a quantitative descriptive survey study that aims to (1) To find out the scientific literacy category of class VIII students at Katumbagan Lemo State Middle School, (2) To find out the scientific literacy ability category of each class VIII at Katumbagan Lemo State Middle School. The population of class VIII students of SMP Negeri Katumbagan Lemo was 81 students. The research instrument was in the form of 20 multiple-choice questions on the main material of the human digestive system. Data collection techniques were by giving tests directly at school. Data are analyzed descriptively. Based on the results of data analysis, it was known that the category of scientific literacy abilities of class VIII students of SMP Negeri Katumbagan Lemo was still classified as Very Low.